RNS parity detection for the two-moduli set 2p − j, 2p + j. Issue 1 (2nd January 2018) - Chen, Chien-Yuan
ABSTRACT: This paper presents a new parity detection technique over the type of two-moduli set for some positive integer p satisfying . Let, where t is an odd number. Given an RNS number on T, we show that the parity of X is, where denotes the sign bit of the number t, if . Otherwise, the parity of X is .